Elasticity modulus monitoring through an ambient vibration response method : application to cement-based pastes - Maia, Lino (2012)
The E-modulus of cement-based materials is a property that experiences a high rate of change at early ages, and its continuous monitoring since casting is fundamental to identify the phase transition from fluid to solid. This paper presents a study with a recently developed non-destructive method for continuous monitoring the E-modulus of cement-based materials since casting. Based on the evaluation of the first resonant frequency of a composite cantilever containing the material under testing, it is possible to detect the E-modulus growth, and also to identify the changes on its evolution due to modifications on the mix composition. Twenty one compositions are tested, encompassing cementitious pastes with five types of cement and five w/c ratios, as well as three different contents of limestone filler, fly ash, silica fume and metakaolin.